2018
DOI: 10.1111/ahe.12423
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related histomorphometric and immunohistochemical changes of the moderator band in Egyptian Baladi cattle

Abstract: The moderator band (MB) is a common fibromuscular anatomical structure for the right ventricle of most animals. The histomorphometric and immunohistochemical analysis of the MBs of Egyptian Baladi cattle in relation to age was the aim of this study. Eighteen clinically healthy animals of both sexes were used for this study. The animals were divided into three groups depending on age, group I (N = 4, <1 year), group II (N = 8, 1–2 years) and group III (N = 6, 4–8 years). Cross sections of the MBs from all gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…In this study, the histological examination of the ST revealed the presence of connective tissue, cardiac muscle fibers, blood vessels, and Purkinje cells in pig heart samples, in agreement with the histological description of the trabeculae in other animal species and in humans 11,16,17,19,32,[43][44][45][46] . It was also evidenced a variation in Purkinje fibers distribution and disposition, besides the proportion between the striated cardiac and connective muscle tissues between the samples.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the histological examination of the ST revealed the presence of connective tissue, cardiac muscle fibers, blood vessels, and Purkinje cells in pig heart samples, in agreement with the histological description of the trabeculae in other animal species and in humans 11,16,17,19,32,[43][44][45][46] . It was also evidenced a variation in Purkinje fibers distribution and disposition, besides the proportion between the striated cardiac and connective muscle tissues between the samples.…”
Section: Discussionsupporting
confidence: 88%